A SERS detector based on shuttle-shaped nanocrystals and its preparation method and application

By depositing high-degree-to-diameter gold-silver alloy shuttle-type nanocrystals on the polyimide film, forming a tight two-dimensional layered structure, the problem of insufficient flexibility and detection sensitivity of existing SERS detectors is solved, and high flexibility is achieved SERS detector with sensitivity, suitable for rapid detection of irregular surfaces.

CN114739978BActive Publication Date: 2025-02-18SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210479704.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-05
Publication Date
2025-02-18
Estimated Expiration
2042-05-05

AI Technical Summary

Technical Problem

Existing SERS detectors lack flexibility and high detection sensitivity, making it difficult to effectively detect trace molecules and environmental pollutants on irregular surfaces.

Method used

Using a SERS detector composed of a polyimide film and a gold-silver alloy shuttle nanocrystalline with a high-degree-to-diameter ratio gold-silver alloy shuttle nanocrystalline is deposited by gas-liquid interface method, and a tight two-dimensional layer is formed by intermolecular forces. Structure to achieve the combination of flexible substrate and high detection sensitivity.

Benefits of technology

The flexible SERS detector is achieved with high sensitivity and signal uniformity, and can quickly and accurately detect pesticide residues on the surface of fruits and vegetables, trace molecules on the surface of the instrument, and environmental pollutants, greatly improving the detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114739978B_ABST
    Figure CN114739978B_ABST
Patent Text Reader

Abstract

The present invention discloses a SERS detector based on shuttle-type nanocrystals, the SERS detector is composed of a polyimide film and shuttle-type nanocrystals; the polyimide film is used as a substrate, the shuttle-type nanocrystals are a core-shell structure, with gold nanorods as the core and a gold-silver alloy as the shell, the shuttle-type nanocrystals are deposited on the polyimide film by a gas-liquid interface method, and the shuttle-type nanocrystals on the polyimide film are closely arranged together by intermolecular forces to form a two-dimensional layered structure. The present invention also discloses a preparation method of the above-mentioned SERS detector and its application in the detection of pesticide residues on the surface of fruits and vegetables, the detection of trace molecules on the surface of utensils, and the quantitative detection of environmental pollutants. The tip of the surface of the high aspect ratio gold-silver alloy heterogeneous shuttle-type nanocrystals in the SERS detector of the present invention will produce a strong inherent electromagnetic field "hot spot" and the high aspect ratio shuttle-type nanoparticles are closely arranged with small gaps between particles, which can greatly enhance the SERS signal of the substance to be detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a SERS detector based on shuttle-shaped nanocrystals, and also relates to a preparation method of the SERS detector and its application in the detection of pesticide residues on fruit and vegetable surfaces, the detection of trace molecules on the surface of objects and the quantitative detection of environmental pollutants. Background Art

[0002] With the continuous development of science and technology, the preparation of nanomaterials has also developed rapidly. Among the precious metal nanomaterials, gold, silver and gold-silver composite nanomaterials have performed particularly well. A large number of studies have shown that the properties of gold and silver nanoparticles are closely related to their morphology. The more anisotropic the particles are, the better the localized surface plasmon resonance (LSPR) and SERS properties they exhibit. Various heterogeneous precious metal nanocrystals have also been reported, such as gold-silver nanospheres, gold-silver nanobricks, silver nanocones, etc., and have been widely used in environmental pollution detection, surface-enhanced Raman scattering detection, catalysis and other fields.

[0003] Traditional rigid SERS substrates lack flexibility and are difficult to fully contact with the surface of the object to be detected, which limits the detection application of SERS substrates in actual scenarios. Based on this limitation, people have proposed flexible substrates, which use flexible materials to achieve the bendability of the substrate. Compared with rigid substrates, flexible substrates are bendable, highly flexible, and can be adsorbed on any complex surface for in-situ detection. They can quantitatively detect irregular surfaces, greatly improving the detection efficiency. However, constructing flexible materials that have both high sensitivity and signal uniformity and can be transferred in real time is a key difficulty and a technical bottleneck to be solved. Summary of the invention

[0004] Technical problem: One of the objects of the present invention is to provide a SERS detector based on shuttle-shaped nanocrystals that has both flexibility and high detection sensitivity. Another object of the present invention is to provide a method for preparing the above-mentioned SERS detector and its application in the detection of pesticide residues on the surface of fruits and vegetables, the detection of trace molecules on the surface of objects and the quantitative detection of environmental pollutants.

[0005] Technical solution: The SERS detector based on shuttle-shaped nanocrystals described in the present invention is composed of a polyimide film and shuttle-shaped nanocrystals; the polyimide film is used as a substrate, the shuttle-shaped nanocrystals are a core-shell structure, with gold nanorods as the core and a gold-silver alloy as the shell, the shuttle-shaped nanocrystals are deposited on the polyimide film by a gas-liquid interface method, and the shuttle-shaped nanocrystals on the polyimide film are closely arranged together by intermolecular forces to form a two-dimensional layered structure. The shuttle-shaped nanocrystals are combined with the polyimide film by van der Waals forces.

[0006] Wherein, the thickness of the layered structure is the length of the shuttle-shaped nanocrystals.

[0007] The preparation method of the above-mentioned SERS detector based on shuttle-type nanocrystals comprises the following steps:

[0008] (1) mixing a chloroauric acid solution and a hexadecyltrimethylammonium bromide solution, and adding a sodium borohydride solution thereto after mixing to obtain a gold nanorod seed solution; dissolving hexadecyltrimethylammonium bromide and sodium oleate in water at the same time, adding a silver nitrate solution thereto after fully dissolving, and then adding a chloroauric acid solution after mixing, adding concentrated hydrochloric acid to adjust the pH value of the solution after stirring, and finally adding an L-ascorbic acid solution to obtain a growth solution; adding the gold nanorod seed solution to the growth solution, and obtaining a solution containing gold nanorods after growth;

[0009] (2) centrifuging the solution containing the gold nanorods, adding the gold nanorods to an aqueous solution of hexadecyltrimethylammonium bromide to redissolve them to obtain a reaction solution, sequentially adding a glycine solution, a sodium hydroxide solution, a chloroauric acid solution, a silver nitrate solution, and an L-ascorbic acid solution to the reaction solution, and obtaining, after reaction, shuttle-shaped nanocrystals having the gold nanorods as cores and a gold-silver alloy as shells;

[0010] (3) centrifuging the shuttle-shaped nanocrystals, adding them to pure water for redissolution to obtain a shuttle-shaped nanocrystal solution; adding a tetrahydrofuran solution of polystyrene to the shuttle-shaped nanocrystal solution, mixing well, and shaking at room temperature overnight to allow PS to fully replace hexadecyltrimethylammonium bromide on the surface of the shuttle-shaped nanocrystals;

[0011] (4) A two-dimensional layered structure formed by shuttle-shaped nanocrystals was constructed on a polyimide film using the gas-liquid interface self-assembly method to obtain a SERS detector.

[0012] In step (2), the pH value of the mixed reaction solution is adjusted to 8-9 by using a sodium hydroxide solution. A pH value of 8-9 can better enable gold and silver ions to alternately deposit and grow on the rod to form a shuttle-shaped gold-silver alloy shell layer.

[0013] Wherein, in step (2), the aspect ratio of the shuttle-shaped nanocrystals is 3 to 5.

[0014] The above-mentioned SERS detector based on shuttle-shaped nanocrystals is applied in the detection of pesticide residues on the surface of fruits and vegetables, the detection of trace molecules on the surface of objects and the quantitative detection of environmental pollutants.

[0015] The specific application process is as follows: press the SERS detector onto the surface of the object to be tested, remove the polyimide film after pressing, transfer the two-dimensional layered structure formed by the shuttle-shaped nanocrystals to the surface of the object to be tested without loss, and use a handheld Raman spectrometer to irradiate the surface of the object to be tested for immediate detection and analysis.

[0016] Beneficial effects: The tips of the surfaces of the high aspect ratio gold-silver alloy heterogeneous shuttle-shaped nanocrystals in the SERS detector of the present invention will produce strong inherent electromagnetic field "hot spots" (the tip effect of plasmon coupling can form strong inherent electromagnetic field "hot spots"), and the high aspect ratio shuttle-shaped nanoparticles are closely arranged with small gaps between particles, thereby realizing a unique surface enhanced Raman sensitization effect of dual superposition of local electromagnetic field hot spots and particle gap hot spots, thereby greatly enhancing the SERS signal of the substance to be detected. Since the SERS signal of the substance to be detected is enhanced, the detection sensitivity of the substance to be detected is greatly improved, the detection lower limit is reduced, and it can be used for trace substance detection; the SERS detector of the present invention adopts a flexible substrate that can be used for the detection of irregular surfaces, is bendable and foldable, and has a high degree of fit with the surface of the object to be detected, thereby greatly improving the detection efficiency; the SERS detector of the present invention can quickly detect the object to be detected, and is suitable for large-scale on-site detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The UV-visible absorption spectra of high aspect ratio gold nanorods and heterogeneous gold-silver shuttle nanocrystals;

[0018] Figure 2 The transmission electron microscope image of the polyimide film composited with gold and silver nanocrystals; Figure 2 a is a transmission electron microscope image of a SERS detector formed by combining the short and thick nanocrystals prepared in Comparative Example 1 with a polyimide film; Figure 2 b is a transmission electron microscopy image of a SERS detector formed by combining the shuttle-shaped nanocrystals prepared in Example 1 with a polyimide film;

[0019] Figure 3 The Raman signal curves of the SERS detectors prepared in Example 1 and Comparative Example 1 are of the nano-shuttle film with a high aspect ratio and the film with an aspect ratio of 1 at the same substrate concentration;

[0020] Figure 4 (A) is the Raman detection signal of the SERS detector of the present invention for 4-aminophenol (4-ATP) solutions with different concentrations; (B) is the Raman detection signal of 20 different detection points under the same concentration of 4-ATP solution;

[0021] Figure 5 Schematic diagram of the instant and highly sensitive detection process for surface pollutants on objects with complex morphology. DETAILED DESCRIPTION

[0022] Example 1

[0023] The preparation method of the SERS detector based on shuttle-type nanocrystals of the present invention specifically comprises the following steps:

[0024] (1) Synthesis of gold seeds: 5 mL of 0.2 M hexadecyltrimethylammonium bromide aqueous solution was placed in a beaker, and 5 mL of 1 mM chloroauric acid solution was added thereto. After thorough mixing, 0.6 mL of 10 mM sodium borohydride aqueous solution prepared with ice water was quickly added. The mixture was stirred rapidly for 2 to 3 min and then allowed to stand at room temperature for 1 h to obtain a gold nanorod seed solution for use.

[0025] (2) Synthesis of high aspect ratio gold nanorods: 0.7 g of hexadecyltrimethylammonium bromide and 0.123 g of sodium oleate were added to 25 mL of deionized water to obtain a mixed solution. The mixed solution was placed in a 30°C constant temperature water bath. After the solid was fully dissolved, 1 mL of 25 mM chloroauric acid solution and 2.4 mL of 4 mM silver nitrate solution were added thereto. After thorough mixing, the mixture was stirred for 15 min. Then, 0.9 mL of concentrated hydrochloric acid was added and stirred for 15 min. During the vigorous stirring, 0.01 mL of 0.08 M ascorbic acid solution was added. After stirring, a growth solution was obtained. 0.012 mL of gold nanorod seed solution was added to the growth solution. After thorough mixing, the mixed solution was placed in a 25-30°C water bath for 2 h to obtain a solution containing gold nanorods. Its UV-visible absorption spectrum is shown in FIG. Figure 1 As shown;

[0026] (3) Synthesis of heterogeneous gold-silver shuttle-shaped nanocrystals with high aspect ratio: 5 mL of the solution containing gold nanorods in step 1 was centrifuged twice (each time at 6500 rpm for 10 min) to remove excess reactants. After centrifugation, an equal volume (the same volume as the removed supernatant, specifically 5 mL) of 0.2 M hexadecyltrimethylammonium bromide aqueous solution was added to dissolve the mixture to obtain a reaction solution; 5 mL of the purified gold nanorods was mixed with 5 mL of glycine solution (0.05 M), and then 30 uL of sodium hydroxide solution (the concentration of the sodium hydroxide solution was 2 M) was added. Under vigorous stirring, 0.2 mL of 0.025 M chloroauric acid solution, 0.2 mL of 0.04 M silver nitrate solution, and 0.08 mL of 0.08 M ascorbic acid solution were added in sequence. The reaction was allowed to stand for 1 h to obtain shuttle-shaped nanocrystals with gold nanorods as cores and gold-silver alloy as shells; the aspect ratio of the shuttle-shaped nanocrystals was 4;

[0027] (4) 10 mL of the solution containing shuttle-shaped nanocrystals in step (3) was centrifuged at 6500 rpm for 10 min to remove excess reactants. After centrifugation, an equal volume (equal to the volume of the excess reaction solution removed, specifically 10 mL) of pure water was added to re-dissolve the solution to obtain a shuttle-shaped nanocrystal solution, which was stored at 4° C. The ultraviolet absorption spectrum thereof was as follows: Figure 1 As shown, the heterogeneous gold-silver shuttle nanocrystals have two absorption peaks like gold nanorods, and their ultraviolet absorption spectrum is blue-shifted compared to that of gold nanorods.

[0028] (5) 9 mL of the shuttle-type nanocrystal solution was evenly dispersed into 6 1.5 mL centrifuge tubes, and the supernatant was removed by centrifugation. 1 mL of a 2 mg / mL monothiol-terminated polystyrene (the number average molecular weight of the polystyrene was Mn=50,000) tetrahydrofuran solution was added to the centrifuge tube from which the supernatant was removed, and the mixture was mixed and shaken overnight at room temperature to allow the polystyrene to fully replace the hexadecyltrimethylammonium bromide on the surface of the heterogeneous gold-silver shuttle-type nanocrystals;

[0029] (6) After centrifuging the above solution, remove the supernatant, and then add 1.5 mL of tetrahydrofuran to resuspend the solution. Repeat this process 3 times; centrifuge the resulting solution to remove the supernatant, and then add 1.5 mL of chloroform to resuspend the solution. Repeat this process 3 times. Finally, centrifuge the 6 tubes of solution to remove the supernatant, add 0.2 mL of chloroform to resuspend the solution and put them into a 1.5 mL centrifuge tube. Finally, add a certain amount of chloroform (0.3 mL) to make the total volume of the solution in the centrifuge tube 1.5 mL. After centrifugation again, remove the supernatant as much as possible and shake the bottom of the centrifuge tube to fully dissolve the precipitate in the small amount of remaining chloroform.

[0030] (7) Take a polyimide film with an area of ​​3×3 cm (the thickness of the polyimide film is 0.055 mm), use a pipette to add 5 μL of deionized water to the polyimide film to form a hemispherical water droplet, use a pipette to absorb the concentrated heterogeneous gold-silver shuttle-type nanocrystal solution in step (6), and add 0.5 μL to the surface of the water droplet. The heterogeneous gold-silver shuttle-type nanocrystals spontaneously form a dense two-dimensional structure on the surface of the water droplet. When the water droplet is completely evaporated, a micro-nano sequenced assembled film (detection film) composited with the polyimide film is obtained, which is a SERS detector. Its transmission electron microscope morphology is shown in FIG. Figure 2 As shown, from its morphology, it can be seen that the shuttle-shaped particles with high aspect ratio are closely arranged to form a dense detection film, showing its structural integrity and order at the nanoscale.

[0031] The Raman enhancement effect of the micro-nano ordered assembled film prepared in Example 1 was evaluated (using 4-ATP as the probe molecule): the prepared detection film (with a silicon wafer as the substrate) was placed in 1 mL of 4-ATP ethanol solution with concentrations of 0.1 nM, 1 nM, 10 nM, 100 nM, and 0.1 μM for overnight soaking, the substrate was taken out, and after it was naturally dried, it was placed under a Raman spectrometer for measurement. The obtained spectra were compared for intensity, and the 1078 cm -1 The peak intensity of the characteristic peak is used as the reference peak position to compare the Raman enhanced detection signals of different concentrations of 4-ATP, such as Figure 4 As shown in A. Adjust the position of the sample and select 20 points for measurement (such as Figure 4 B), from Figure 4As can be seen in B, the uniformity of the SERS detector can be prepared and used on a large scale (the SERS detector can have the same signal when performing laser detection at any location, avoiding the existence of false positives in the detection results, and the uniform detection film can achieve the accuracy of multiple detections). Here, a rigid substrate silicon wafer is selected for the Raman performance evaluation. The PI (polyimide) film has the same properties as the silicon wafer, but PI can show stronger flexibility and adhesion, and also has good hydrophobicity and stability, and will not interfere with the object to be measured. It can be seen that the micro-nano sequenced assembly film prepared by the present invention can detect the SERS enhanced signal under the Raman spectrometer, and has high sensitivity, and the minimum detection limit can be as low as 0.1nM.

[0032] Comparative Example 1

[0033] First, prepare nanocrystals with a length-to-diameter ratio of 1:1, with gold nanorods as the core and gold-silver alloy as the shell, and then prepare SERS detectors based on nanocrystals with a length-to-diameter ratio of 1:

[0034] (1) Synthesis of gold seeds: 5 mL of 0.2 M hexadecyltrimethylammonium bromide aqueous solution was placed in a beaker, and 5 mL of 1 mM chloroauric acid solution was added thereto. After thorough mixing, 0.6 mL of 10 mM sodium borohydride aqueous solution prepared with ice water was quickly added. The mixture was stirred rapidly for 2 to 3 min and then allowed to stand at room temperature for 1 h to obtain a gold nanorod seed solution for use.

[0035] (2) Take 5 mL of 0.2 M hexadecyltrimethylammonium bromide aqueous solution in a 15 mL centrifuge tube, add 5 mL of 1 mM chloroauric acid aqueous solution and 0.2 mL of 4 mM silver nitrate aqueous solution, invert it several times to mix thoroughly, then add 0.08 mL of 80 mM ascorbic acid aqueous solution, invert it 2-3 times, and the solution changes from light yellow to colorless, add 0.012 mL of gold nanorod seed solution, mix thoroughly, and place it in a 25-30 ° C water bath for 2 h to grow;

[0036] (3) Centrifuge 5 mL of the gold nanorods in step (2) twice (6500 rpm, 10 min) to remove excess reactants, and add an equal volume of 0.2 M hexadecyltrimethylammonium bromide aqueous solution to dissolve; take 5 mL of the purified gold nanorod solution and mix it with 5 mL of 0.05 M glycine solution, then add 30 uL of sodium hydroxide (2 M) solution, and then add 0.2 mL of 1 mM chloroauric acid solution, 0.2 mL of 4 mM silver nitrate solution and 0.08 mL of 80 mM ascorbic acid solution under vigorous stirring, let it react for 1 h, and finally centrifuge the prepared gold and silver nanocrystals at 6500 rpm for 10 min to remove excess reactants, then add an equal volume of pure water to dissolve, and store at 4°C;

[0037] (4) 9 mL of the nanocrystal solution was evenly dispersed into 6 1.5 mL centrifuge tubes, and the supernatant was removed by centrifugation. 1 mL of a 2 mg / mL monothiol-terminated polystyrene (the number average molecular weight of the polystyrene was Mn=50,000) tetrahydrofuran solution was added to the centrifuge tube from which the supernatant was removed, and the mixture was mixed and shaken overnight at room temperature to allow the polystyrene to fully replace the hexadecyltrimethylammonium bromide on the surface of the heterogeneous gold and silver nanocrystals;

[0038] (5) After centrifuging the above solution, remove the supernatant, and then add 1.5 mL of tetrahydrofuran to resuspend the solution. Repeat this process 3 times; after centrifuging the resulting solution, remove the supernatant, and then add 1.5 mL of chloroform to resuspend the solution. Repeat this process 3 times. Finally, after centrifuging the 6 tubes of solution to remove the supernatant, add 0.2 mL of chloroform to resuspend the solution and put it into a 1.5 mL centrifuge tube. Finally, add a certain amount of chloroform (0.3 mL) to make the total volume of the solution in the centrifuge tube 1.5 mL. After centrifugation again, remove the supernatant as much as possible and shake the bottom of the centrifuge tube to fully dissolve the precipitate in the small amount of remaining chloroform.

[0039] (6) Take a polyimide film with an area of ​​3×3 cm and a thickness of 0.055 mm, and use a pipette to drip 5 μL of deionized water onto the polyimide film to form a hemispherical water droplet. Use a pipette to absorb the concentrated heterogeneous gold and silver nanocrystal solution in step (6), and drip 0.5 μL onto the surface of the water droplet. The heterogeneous gold and silver nanocrystals spontaneously form a two-dimensional structure on the surface of the water droplet. After the water droplet is completely evaporated, a heterogeneous gold and silver nanocrystal layer (the heterogeneous gold and silver nanocrystal layer is the detection film) on the polyimide film is obtained. The transmission electron microscope morphology is shown in the following figure. Figure 2 As shown in a, from its morphology, it can be seen that the particles with an aspect ratio of 1 are short and thick, and the two ends are not as "sharp" as the high aspect ratio, so the hot spots generated are also smaller. In addition, compared with the short and thick particles of 1:1, the slender grains with a high aspect ratio can be closely arranged to form a dense film, while the film of 1:1 shows stacking and other phenomena. The film formed by 1:1 will be unstable during the detection process, resulting in deviations and other problems. In addition Figure 3 The Raman signal curves of the nano shuttle film with high aspect ratio and the film with aspect ratio 1 at the same concentration are shown in Fig. Figure 3 It is also clear that the signal in a is much higher than that in b. Therefore, the high aspect ratio shuttle-shaped nanoparticle film at the nanoscale shows its structural integrity and order.

[0040] The SERS detector prepared in Example 1 is used to simulate the real-world environment for the high-sensitivity detection of pollutants by spraying and transferring the complex morphology of the test object surface: the washed apple skin is sprayed with distilled water, then with anhydrous ethanol, and then with the diluted thiram solution. After the apple skin is dried, the detection process in the simulated real environment is performed. First, the SERS detector is attached to the apple skin, and the polyimide film is removed after 5 seconds. At this time, the micro-nano sequence assembly film is transferred to the skin surface without loss. The apple skin is immediately detected by handheld Raman. Figure 4 In the figure, we can see that the flexible substrate adheres to the surface of the object with complex morphology such as apples, and can form a local enhanced electromagnetic field hotspot with high sensitivity and signal uniformity, which can be used for on-site instant and rapid detection of molecules such as pesticide residues in actual environments.

[0041] The present invention is based on synthesizing gold-silver bimetallic shuttle-shaped nanocrystals with high aspect ratio to construct a flexible film material with a multi-level ordered assembly superlattice structure at a micro-nano scale. The shuttle-shaped nanocrystals have uniform morphology and ordered arrangement between particles at the nanometer scale; the order structure of large-area particles is at the micrometer-centimeter scale; the nanometer-level ordered arrangement ensures hot spot enhancement and signal sensitivity, and the centimeter-level order ensures signal uniformity and uses polyimide flexible materials to composite with it to prepare a surface enhanced Raman (SERS) detection device with high signal sensitivity and uniformity. The basic element of the flexible SERS sensing detection device is a shuttle-shaped nanocrystal with a gold nanorod as the core, which is reduced by glycine in an alkaline environment (pH=8-9) to form a gold-silver alloy core-shell. The shuttle-shaped nanocrystal is then used as a basic building unit, and after surface functionalization and modification of a polymer ligand, it is self-assembled at the gas-liquid interface of a flexible polyimide film as a substrate to form a two-dimensional superlattice film. The present invention can realize instant transfer of the detection film on the polyimide film to the surface of fruits, vegetables and objects with complex topological structures to be tested, thereby realizing rapid, highly sensitive and real-time detection of pollutant molecules such as pesticide residues and thiram on the surface of the objects to be tested, and the detection process can be completed within 10 seconds.

Claims

1. A SERS detector based on shuttle-type nanocrystals, characterized in that: The SERS detector is composed of a polyimide film and shuttle-shaped nanocrystals; the polyimide film is used as a substrate, and the shuttle-shaped nanocrystals are a core-shell structure with gold nanorods as the core and a gold-silver alloy as the shell. The shuttle-shaped nanocrystals are deposited on the polyimide film by a gas-liquid interface method, and the shuttle-shaped nanocrystals on the polyimide film are closely arranged together by intermolecular forces to form a two-dimensional layered structure.

2. The SERS detector based on shuttle-type nanocrystals according to claim 1, characterized in that: The thickness of the layered structure is the length of the shuttle-shaped nanocrystal.

3. The method for preparing the SERS detector based on shuttle-type nanocrystals according to claim 1, characterized in that: The steps include: (1) mixing a chloroauric acid solution and a hexadecyltrimethylammonium bromide solution, and then adding a sodium borohydride solution thereto to obtain a gold nanorod seed solution; dissolving hexadecyltrimethylammonium bromide and sodium oleate in water at the same time, and after fully dissolving, adding a silver nitrate solution thereto, mixing well, and then adding a chloroauric acid solution, stirring, and then adding concentrated hydrochloric acid to adjust the pH value of the solution, and finally adding an L-ascorbic acid solution to obtain a growth solution; adding a gold nanorod seed solution into a growth solution to obtain a solution containing gold nanorods after growth; (2) centrifuging the solution containing the gold nanorods, adding the gold nanorods to an aqueous solution of hexadecyltrimethylammonium bromide to redissolve them to obtain a reaction solution, sequentially adding a glycine solution, a sodium hydroxide solution, a chloroauric acid solution, a silver nitrate solution and an L-ascorbic acid solution to the reaction solution, and obtaining, after reaction, shuttle-shaped nanocrystals having the gold nanorods as cores and a gold-silver alloy as shells; (3) centrifuging the shuttle-shaped nanocrystals, adding them to pure water for redissolution to obtain a shuttle-shaped nanocrystal solution; adding a tetrahydrofuran solution of polystyrene to the shuttle-shaped nanocrystal solution, mixing well, and shaking at room temperature overnight to allow the polystyrene to fully replace the hexadecyltrimethylammonium bromide on the surface of the shuttle-shaped nanocrystals; (4) A two-dimensional layered structure composed of shuttle-shaped nanocrystals was constructed on a polyimide film using the gas-liquid interface self-assembly method to obtain a SERS detector.

4. The method for preparing a SERS detector based on shuttle-type nanocrystals according to claim 3, characterized in that: In step (2), the pH value of the mixed reaction liquid is adjusted to 8-9 by adding sodium hydroxide solution.

5. The method for preparing a SERS detector based on shuttle-type nanocrystals according to claim 3, characterized in that: In step (2), the aspect ratio of the shuttle-shaped nanocrystals is 3-5.

6. Application of the shuttle-shaped nanocrystal-based SERS detector of claim 1 in the detection of pesticide residues on fruit and vegetable surfaces, the detection of trace molecules on the surface of objects, and the quantitative detection of environmental pollutants.

7. The use of the shuttle-shaped nanocrystal-based SERS detector according to claim 6 in the detection of pesticide residues on fruit and vegetable surfaces, the detection of trace molecules on the surface of objects, and the quantitative detection of environmental pollutants, characterized in that: The specific application process is: press the SERS detector to the surface of the object to be tested, remove the polyimide film after pressing, and transfer the two-dimensional layered structure formed by the shuttle-shaped nanocrystals to the surface of the object to be tested without loss, and use a handheld Raman spectrometer to irradiate the surface of the object to be tested for immediate detection and analysis.

Citation Information

Patent Citations

  • Two-dimensional flexible precious metal nanoparticle superlattice film and construction method and application thereof

    CN110899720A

  • Preparation method of surface-enhanced Raman scattering substrate

    CN112499581A